Physical-mechanical characterization of moriche natural fibre (Mauritia flexuosa) and composite with bio-epoxy resin - Mora Espinosa, William Javier (Strojniški vestnik, 2019)
The characterization of natural fibres is currently used in the field of science and engineering of materials with the purpose of developing new bio-composites friendly to the environment. The goal of this research is to manufacture and characterize a bio-composite reinforced with Moriche palm fibre (Mauritia flexuosa) and to determine the thermal, mechanical and morphological properties of the fibre. Subsequently, the tensile and flexion properties of the composite was evaluated, as well as its morphology. The thermogravimetric analysis demonstrated that the fibre has hydrophilic characteristics and good stability at temperatures close to 200 °C. In the tensile test under static axial forces, its modulus of elasticity, stress and maximum deformation was determined. Its morphology, composed of the small lumen and wide cell wall with size variations, was examined with scanning electron microscopy (SEM). In the same way, the maximum tensile stress of the composite leads to the conclusion that it is viable to use this material for applications in non-structural elements, which are below 25 MPa. The results of maximum flexural strength (253.7 MPa) allow more extensive applications in doubly supported or overhanging parts subjected to concentrated or distributed loads. The microstructure obtained with SEM showed a poor adhesion between the matrix and the reinforcement.
Keywords: adhezija; biocomposite; biokompoziti; characterization; matrice; mehanske lastnosti; morfologija; naravna vlakna; natural fibers; ojačitev; reinforcement; toplotna stabilnost